Principles Of Islamic Law In Indonesia Civil Law : A Study Of Obligations In Agreements And Contracts - Harry Tuhumury (PT. Anagata Sembagi Education, 2024)
This study examines the application of Islamic legal principles in Indonesian civil law, with a focus on obligations in agreements and contracts. Although principles of Islamic law, such as Justice (‘adl), transparency (bayan), and the Prohibition of usury, have been applied in some sectors of civil law, there are significant challenges in integrating these two legal systems. This study found harmony in several aspects, such as protection against weak parties to the contract, but there are also discrepancies, especially in freedom of contract which is more emphasized in civil law. In addition, the lack of harmonized regulations and the lack of uniform implementation guidelines often lead to legal conflicts and uncertainty. The study recommends revisions to legislation to accommodate Sharia principles in civil agreements and contracts, as well as the drafting of uniform guidelines for Legal Practitioners. The results of this study are expected to be a theoretical foundation for the development of national law that is more inclusive and relevant to the needs of the Indonesian people.